Predicting American Board of Emergency Medicine Qualifying Examination Passage Using United States Medical Licensing Examination Step Scores - Caffery, Terrell (Ochsner J, 2018)
BACKGROUND: The objective of the current study was to determine whether emergency medicine residents' United States Medical Licensing Examination (USMLE) scores are significantly associated with first-attempt passage of the American Board of Emergency Medicine (ABEM) qualifying (written) examination. We hypothesized that USMLE Step 2 Clinical Knowledge (CK) scores would be useful in predicting students who passed the ABEM qualifying examination on their first attempt. METHODS: For this retrospective cohort study, we examined the data of residents who successfully completed training at two emergency medicine residency programs between the years 2002-2013. Because scores on the USMLE Step examinations varied greatly across years, we obtained means and standard deviations from the National Board of Medical Examiners. We subtracted the mean score for the year each resident took the examination from the resident's examination score, creating centered Step 1 and centered Step 2 CK scores. RESULTS: A multivariate logistic regression analysis indicated that centered Step 2 CK scores could be used to predict the odds of passing the ABEM qualifying examination (odds ratio = 1.05 [95% confidence interval 1.02 to 1.08, P < 0.001]). Using a Step 2 CK score cutoff of 7 points lower than the mean yielded 64% sensitivity and 81% specificity for predicting passage of the ABEM written examination on the first attempt. CONCLUSION: Program directors and selection committees may wish to consider whether applicants' Step 2 CK scores are near the national average when making ranking decisions, as this variable is highly predictive of passing the ABEM qualifying examination on the initial attempt.